9th International conference “Nanobiophysics: fundamental and applied aspects” - Kosevich, M. V.; Karachevtsev, V. O.; Dovbeshko, G. I. (Biophysical Bulletin, 2026)
9th International conference “NANOBIOPHYSICS: Fundamental and Applied Aspects” – NBP-2025 took place on October 6-9, 2025 in Kharkiv, Ukraine, in online format, being organized by B. Verkin Institute for Low Temperature Physics and Engineering of the National Academy of Sciences of Ukraine and the Institute of Physics of the National Academy of Sciences of Ukraine. Previous conferences of the “NanoBioPhysics” series, launched in 2009, were organized on a biennial basis in Kharkiv and Kyiv in rotation. The conference brought together more than 100 participants from 13 countries: Ukraine, the Czech Republic, Estonia, Italy, France, Germany, Lithuania, Poland, the Slovak Republic, Spain, Sweden, the UK, and the USA. A total of 93 keynote, oral, and poster presentations were made. The goal of the conference was to discuss the urgent problems and new results achieved in the scientific field combining biophysics and nanotechnology, embracing nanobiohybrids formed by 1-D or 2-D nanomaterials with bioobjects, properties of biomolecules on nanoparticles and nanostructured surfaces, physical aspects of biomolecular nanosystems, theoretical calculations, computer modeling, and applied aspects of nanobiosystems. A special event within the framework of NBP-2025 was the round table on the topic “History of Biophysics in Kharkiv”, dedicated to the commemoration of outstanding scientists who formed the scientific school of molecular biophysics in the second half of the 20th century, which received recognition in Ukraine and abroad. Memories of them were shared by their students and followers, as well as employees of the biophysical departments of scientific institutions in Kharkiv. A book of abstracts based on NBP-2025 materials has been published.